What is the mechanism behind increased permeation rate of a poorly soluble drug from aqueous dispersions of an amorphous solid dispersion? - Frank, Kerstin J.; Westedt, Ulrich; Rosenblatt, Karin M.; Hölig, Peter; Rosenberg, Jörg; Mägerlein, Markus; Fricker, Gert; Brandl, Martin (Journal of pharmaceutical sciences, 2014)
Our aim was to explore the influence of micelles and microparticles emerging in aqueous dispersions of amorphous solid dispersions (ASDs) on molecular/apparent solubility and Caco-2 permeation. The ASD, prepared by hot-melt extrusion, contained the poorly soluble model drug ABT-102, a hydrophilic polymer, and three surfactants. Aqueous dispersions of the ASD were investigated at two concentrations, one above and one close to the critical micelle concentration of the surfactants blend in the extrudate. Micelles were detected at the higher concentration and no micelles at the lower concentration. Apparent solubility of ABT-102 was 20-fold higher in concentrated than in diluted dispersions, because of micelles. In contrast, Caco-2 permeation of ABT-102 was independent of the ASD concentration, but three times faster than that of crystalline suspensions. Molecular solubility of ABT-102 (equilibrium dialysis) was also independent of the ASD concentration, but by a factor 2 higher than crystalline ABT-102. The total amount of ABT-102 accumulated in the acceptor during Caco-2 experiments exceeded the initial amount of molecularly dissolved drug in the donor. This may indicate that dissolution of amorphous microparticles present in aqueous dispersions induces lasting supersaturation maintaining enhanced permeation. The hypothesis is supported by a slower drug permeation when the microparticles were removed. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1779-1786, 2014
Available online 3 January 2016
Gesehen am 18.08.2020